Rare-earth nickelates RNiO3: thin films and heterostructures. (14th February 2018) - Catalano, S; Gibert, M; Fowlie, J; Íñiguez, J; Triscone, J-M; Kreisel, J
Abstract: This review stands in the larger framework of functional materials by focussing on heterostructures of rare-earth nickelates, described by the chemical formula R NiO3 where R is a trivalent rare-earth R   =  La, Pr, Nd, Sm, …, Lu. Nickelates are characterized by a rich phase diagram of structural and physical properties and serve as a benchmark for the physics of phase transitions in correlated oxides where electron–lattice coupling plays a key role. Much of the recent interest in nickelates concerns heterostructures, that is single layers of thin film, multilayers or superlattices, with the general objective of modulating their physical properties through strain control, confinement or interface effects. We will discuss the extensive studies on nickelate heterostructures as well as outline different approaches to tuning and controlling their physical properties and, finally, review application concepts for future devices.